POLICY EFFECTIVENESS OF COMMUNITY-BASED WASTE MANAGEMENT IN THE CITY KEDIRI - Yenik Pujowati (International Journal of Social Science, 2021)
Background; Community consumption patterns contribute to creating increasingly diverse types of waste and the total waste produced, as well as the lack of public awareness in community-based waste management. The policy of the local government of the city of Kediri to provide infrastructure for waste management includes; storage, collection, transfer, transportation and final disposal (TPA). The role of the DLHKP in Kediri City is to provide training and assistance aimed at training residents so that they can use waste and manage waste wisely, especially household waste. Research methods; This type of research uses descriptive and qualitative approaches, researchers try to describe the object of research through observation and analysis of primary data and secondary data. The results of this study indicate that the implementation of community-based waste management socialization in Kediri City has not run optimally. Regarding the infrastructure for the pattern of waste transportation in the city of Kediri, it has not been running effectively and efficiently, due to the lack of a waste transport fleet and limited human resources in the field of waste experts. Conclusion; the effectiveness of community-based waste management policies in the city of Kediri, there are still few people who take part in the waste management process because people do not really understand the concept of waste management